Representations of environmental issues in the documentary film (Al-Academy, 2025)
The modern documentary film is no longer confined by conventional norms, whether in terms of production or theory. Its ongoing development has been accompanied by an increasing capacity to both influence and be influenced by reality, evolving toward aesthetic processes that reflect diverse ideas and issues across the spectrum of life topics it documents—achieving the highest possible degree of credibility. In this context, a profound convergence has emerged between environmental subjects and documentary film, driven by the image’s ability to convey reality, as well as by the aesthetic potential and compositional richness that environmental themes inherently possess. These qualities have endowed the documentary image with highly expressive formal and aesthetic capacities, allowing it to effectively portray a range of topics that require thoughtful examination.Based on this, the research problem is defined as follows: How are environmental issues represented in contemporary documentary film? The significance and objective of the study lie in uncovering and analyzing these representations.The theoretical framework is divided into three main sections:The Concept of Environment in Documentary FilmEnvironmental Issues in Documentary FilmThe Aesthetic Form in Environmental DocumentariesThe third chapter outlines the research methodology, which involves the purposive selection and analysis of the Arabic-language documentary film "Climate Crisis: The Story of Four Girls Fighting Global Environmental Disasters", produced by the German broadcaster DW. The research concludes with a set of key findings, conclusions, and recommendations.